The impact of the COVID‐19 pandemic on people with diabetes and diabetes services: A pan‐European survey of diabetes specialist nurses undertaken by the Foundation of European Nurses in Diabetes survey consortium. Issue 5 (30th December 2020) - Forde, Rita; Arente, Liga; Ausili, Davide; De Backer, Kristin; Due‐Christensen, Mette; Epps, Amanda; Fitzpatrick, Anne; Grixti, Moira; Groen, Sijda; Halkoaho, Arja; Huber, Claudia; Iversen, Marjolein M.; et al.
Abstract: Aim: To describe diabetes nurses' perspectives on the impact of the COVID‐19 pandemic on people with diabetes and diabetes services across Europe. Methods: An online survey developed using a rapid Delphi method. The survey was translated into 17 different languages and disseminated electronically in 27 countries via national diabetes nurse networks. Results: Survey responses from 1829 diabetes nurses were included in the analysis. The responses indicated that 28% (n = 504) and 48% (n = 873) of diabetes nurses felt the COVID‐19 pandemic had impacted 'a lot' on the physical and psychological risks of people with diabetes, respectively. The following clinical problems were identified as having increased 'a lot': anxiety 82% (n = 1486); diabetes distress 65% (n = 1189); depression 49% (n = 893); acute hyperglycaemia 39% (n = 710) and foot complications 18% (n = 323). Forty‐seven percent (n = 771) of respondents identified that the level of care provided to people with diabetes had declined either extremely or quite severely. Self‐management support, diabetes education and psychological support were rated by diabetes nurse respondents as having declined extremely or quite severely during the COVID‐19 pandemic by 31% (n = 499), 63% (n = 1, 027) and 34% (n = 551), respectively. Conclusion: The findings show that diabetes nurses across Europe have seen significant increases in both physical and psychological problems in their patient populations during COVID‐19. The data also show that clinical diabetes services have been significantly disrupted. As the COVID‐19 situation continues, we need to adapt care systems with some urgency to minimise the impact of the pandemic on the diabetes population.